Atmospheric pressure chemical ionization mass spectrometry at low flow rates: Importance of ion source housing - Strmeň, Timotej; Vrkoslav, Vladimír; Bosáková, Zuzana; Cvačka, Josef (Rapid communications in mass spectrometry, 2020)
RATIONALE: Hyphenation of atmospheric pressure chemical ionization (APCI) mass spectrometry with capillary and micro high-performance liquid chromatography (HPLC) is attractive for many applications, but reliable ion sources dedicated to these conditions are still missing. There are a number of aspects to consider when designing such an ion source, including the susceptibility of the ionization processes to ambient conditions. Here we discuss the importance of ion source housing for APCI at low flow rates. METHODS: Selected compounds dissolved in various solvents were used to study ionization reactions at 10 μL/min flow rate. APCI spectra were generated using the Ion Max-S source (Thermo Fisher Scientific) operated with or without the ion source housing. RESULTS: The APCI spectra of most compounds measured in the open and enclosed ion sources were markedly different. The differences were explained by water and oxygen molecules that entered the plasma region of the open ion source. Water tended to suppress charge transfer processes while oxygen diminished electron capture reactions and prevented the formation of acetonitrile-related radical cations useful for localizing double bonds in lipids. The effects associated with the ion source housing were significantly less important for compounds that are easy to protonate or deprotonate. CONCLUSIONS: The use of ion source housing prevented alternative ionization channels leading to unwanted or unexpected ions. Compared with the conventional flow rate mode (1 mL/min), the effects of ambient air components were significantly higher at 10 μL/min, emphasizing the need for ion source housing in APCI sources dedicated to low flow rates.